simplify your answer.

Algebra
Tutor: None Selected Time limit: 1 Day

Jun 16th, 2015

Thank you for the opportunity to help you with your question!

the exponentials in the denominator can add up since the base (b) are the same.

=b^(1/3)/b^[(-1/2)+(1/4)]

=b^(1/3)/b^(-1/4)

from the rule of exponentials; 1/a^2=a^(-2), then 1/b^(-1/4)=b^(1/4)

=b^(1/3)*b^(1/4)

=b^[(1/3)+(1/4)]

=b^(7/12)

Please let me know if you need any clarification. I'm always happy to answer your questions.
Jun 16th, 2015

Did you know? You can earn $20 for every friend you invite to Studypool!
Click here to
Refer a Friend
...
Jun 16th, 2015
...
Jun 16th, 2015
May 29th, 2017
check_circle
Mark as Final Answer
check_circle
Unmark as Final Answer
check_circle
Final Answer

Secure Information

Content will be erased after question is completed.

check_circle
Final Answer